IOT-based smart socket system - Leow, Pei Hui (2023)
Electrical Wall Outlet is an essential device for supplying electricity to residential, commercial and industrial users. In light of the escalating demand for energy due to population expansion, minimizing wastage and overconsumption has become a pressing issue. Additionally, malfunctioning wall outlets could be one of the contributing factors to hazardous situations such as fires or electrocution. To address these issues, a Smart Socket System with remote control and real-time current measuring features has been proposed for residential and commercial/industrial settings. The ESP32 microprocessor serves as the system’s core, controlling the ACS712-20A current sensor and relay module to enable smart socket functionality. A Node-red user interface (UI) is designed comprising MQTT protocol and Raspberry Pi microcomputer serving as the server. A Long Short-Term Memory (LSTM) AI Model was utilized to forecast hourly power consumption for the succeeding day, based on data collected and stored in Firebase Database. To enhance safety, a child-safe feature was added that notifies the user to switch off the socket remotely during no-load conditions. Additionally, an Over-the-Air (OTA) update was implemented to enable remote system debugging. In this project, the system’s performance has been evaluated and found to be satisfactory.